Digital light processing (DLP) 3D printing technique applied in the fabrication of two-layered tablets: the concept of a combined polypill - Adamov, Ivana; Medarević, Djordje; Ivković, Branka; Ivković, Aleksandar; Ibrić, Svetlana (Archives of Pharmacy, 2022)
Ever since 3D printing was introduced to the field of pharmacy, it has caused a paradigm shift from the manufacturing of large-scale to small batches of medicines tailored accordingly to the specific needs of patients. This study aimed to formulate and fabricate two-layered 3D tablets using the digital light processing (DLP) technique. Hydrochlorothiazide (HHT,5%,w/w) and warfarin sodium (WS,5%,w/w) were selected as model drugs. The printing process was initiated with 0.1% of photoinitiator, at a constant ratio of poly(ethylene glycol)diacrylate and poly(ethylene glycol) 400, 1:1, with the addition of water (10%,w/w). Single-layered tablets of 8.00 mm diameter and 1.50 mm thickness, containing HHT and WS respectively, were successfully printed, as well as combined two-layered 3D tablets, with each of the active substances in separate layers. Dissolution tests of single-layered tablets showed immediate, but incomplete release of WS (81.47±1.47%, after 45min), and prolonged and complete release of HHT (98.17±3.11%, after 8h), while significantly slower and incomplete release of both drugs from the combined two-layered 3D tablets was observed. The absence of drug-polymer interaction and presence of a layered cross-sectional tablet structure were confirmed. DLP technique enables simple and rapid fabrication of combined two-layered 3D tablets, while further optimization of formulation factors is necessary to achieve complete drug release.
Keywords: DLP technique; hydrochlorothiazide; warfarin sodium; combined two-layered 3D tablets; personalized medicine